2019
DOI: 10.1021/acs.jpcb.8b09913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strongly Coupled Vibration–Cavity Polaritons on the Bulk Vibrational States within a Wavelength-Scale Cavity

Abstract: A Rabi splitting of 43.0 ± 1.0 cm −1 (95% conf.) was determined for the interaction of the CD 3 deformation, the strongest fundamental vibration of the liquid CD 3 CN molecule and fringe modes of a parallel-plate Fabry−Peŕot cavity containing this liquid. Note that vibration−cavity polaritons are also called dressed states, hybrid or mixed states. Since the experimental configuration has many orders of magnitude more vibrational oscillators than photons, vibrational oscillators not in dressed states far outnu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…From the population of vibrationally excited states at thermal equilibrium, a tiny fraction would be allocated to the polariton modes, with the overwhelming majority residing in the dark-state reservoir [17][18][19][20], unless the temperature is low enough for the lower polariton to overtake the predominant population second to that of the ground * joelyuen@ucsd.edu FIG. 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the population of vibrationally excited states at thermal equilibrium, a tiny fraction would be allocated to the polariton modes, with the overwhelming majority residing in the dark-state reservoir [17][18][19][20], unless the temperature is low enough for the lower polariton to overtake the predominant population second to that of the ground * joelyuen@ucsd.edu FIG. 1.…”
Section: Introductionmentioning
confidence: 99%
“…This coupling leads to two polaritonic modes and a macroscopic set of quasi-degenerate dark (subradiant) modes that, to a good approximation, should feature chemical dynamics that is indistinguishable from that of the bare molecular modes [16]. This picture could potentially change as a consequence of ultrastrong coupling effects; however, these effects should not be significant for modest Rabi splittings as those observed in the experiments [12][13][14][15].From the population of vibrationally excited states at thermal equilibrium, a tiny fraction would be allocated to the polariton modes, with the overwhelming majority residing in the dark-state reservoir [17][18][19][20], unless the temperature is low enough for the lower polariton to overtake the predominant population second to that of the ground * joelyuen@ucsd.edu FIG. 1.…”
mentioning
confidence: 99%
“…1 These observations are reminiscent of the description of light-matter coupling in terms of hybrid states known as polaritons, [7][8][9][10][11][12] which successfully explains the optical properties of these systems. [13][14][15][16][17] Recently, it has been suggested that a class of nonadiabatic charge transfer reactions would experience a catalytic effect from resonant collective coupling between high-frequency modes and infrared cavity modes; the mechanism relies on the formation of vibrational polaritons which feature reduced activation energies compared to the bare molecules. 18,19 However, a large class of reactions fall in the adiabatic regime, where the potential energy surfaces of the electronic ground and excited states are well-separated.…”
Section: Introductionmentioning
confidence: 99%
“…19,23 An alternative scheme proposed to increase the Raman scattering cross-section is vibrational strong coupling (VSC), [32][33][34] which is realized when dipole active MVs strongly couple with the vacuum electric field of a microcavity. [35][36][37][38][39][40][41][42][43] VSC results in the formation of vibrational polaritons (VP + and VP À ), separated by the Rabi splitting energy ( hO R , Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Shalabney et al 35 and Long and Simpkins 36 independently showed the formation of vibrational polaritons by coupling the CQO stretching modes of polyvinyl acetate and polymethyl methacrylate films with Fabry-Pérot cavity modes, respectively. Since then, VSC has been demonstrated for many systems such as neat liquids, 38,39 solutions, 40 ionic liquid crystals, 41 protein vibrational modes 42 and multimode vibrational transitions of a polymer. 43 Experimentally, the VP + and VP À states can be observed in the transmission spectrum of the coupled system, as two new peaks with energies shifted from the original frequency by half the Rabi splitting.…”
Section: Introductionmentioning
confidence: 99%